Answers

2016-05-01T00:23:32+05:30
The solution for this question can be seen in the attachment given below..
2 5 2
Comment has been deleted
lolzzzz parthhhjiiiiii.... By the way i know who the one u mentioned.. Thank uu :P
2016-05-01T15:09:08+05:30
We know that,

Dividend = (Divisor × quotient) + Remainder

Now substitute it in it.

4x⁴ - 5x³ - 39x² - 46x - 2 = [g(x) × (x² - 3x - 5)] + (-5x + 8)

4x⁴ - 5x³ - 39x² - 46x - 2 + 5x - 8 = g(x) × (x² - 3x - 5)

4x⁴ - 5x³ - 39x² - 41x - 10 = g(x) × (x² - 3x - 5)

g(x) = 4x⁴ - 5x³ - 39x² - 41x - 10 / (x² - 3x - 5)

After solving, the answer will be,
4x² + 7x + 2
1 5 1